Direct Comparison of Immunogenicity Induced by 10- or 13-Valent Pneumococcal Conjugate Vaccine around the 11-Month Booster in Dutch Infants. - Alienke J Wijmenga-Monsuur; Els van Westen; Mirjam J Knol; Riet M C Jongerius; Marta Zancolli; David Goldblatt; Pieter G M van Gageldonk; Irina Tcherniaeva; Guy A M Berbers; Nynke Y Rots (PLoS ONE)
Background & aims Since 2009/10, a 10- and a 13-valent pneumococcal conjugate vaccine (PCV) are available, but only the 10-valent vaccine is now being used for the children in the Netherlands. As the vaccines differ in number of serotypes, antigen concentration, and carrier proteins this study was designed to directly compare quantity and quality of the antibody responses induced by PCV10 and PCV13 before and after the 11-month booster. Methods Dutch infants (n = 132) were immunized with either PCV10 or PCV13 and DTaP-IPV-Hib-HepB at the age of 2, 3, 4 and 11 months. Blood samples were collected pre-booster and post-booster at one week and one month post-booster for quantitative and qualitative immunogenicity against 13 pneumococcal serotypes, as well as quantitative immunogenicity against diphtheria, tetanus, pertussis and Haemophilus influenzae type b. We compared immunogenicity induced by PCV13 and PCV10 for their ten shared serotypes. Results One month post-booster, pneumococcal serotype-specific IgG geometric mean concentrations (GMCs) for the PCV13 group were higher compared with the PCV10 group for six serotypes, although avidity was lower. Serotype 19F showed the most distinct difference in IgG and, in contrast to other serotypes, its avidity was higher in the PCV13 group. One week post-booster, opsonophagocytosis for serotype 19F did not differ significantly between the PCV10- and the PCV13 group. Conclusion Both PCV10 and PCV13 were immunogenic and induced a booster response. Compared to the PCV10 group, the PCV13 group showed higher levels for serotype 19F GMCs and avidity, pre- as well as post-booster, although opsonophagocytosis did not differ significantly between groups. In our study, avidity is not correlated to opsonophagocytotic activity (OPA) and correlations between IgG and OPA differ per serotype. Therefore, besides assays to determine IgG GMCs, assays to detect opsonophagocytotic activity, i.e., the actual killing of the pneumococcus, are important for PCV evaluation. How differences between the two vaccines relate to long-term protection requires further investigation. Trial registration www.trialregister.nl NTR3069.